Mechanism of model pile installation by water jet fluidization in sand. (15th December 2018) - Passini, Larissa de Brum; Schnaid, Fernando; Rocha, Marcelo Maia; Möller, Sergio Viçosa
Abstract: The present paper discusses the mechanism of pile installation by soil fluidization in saturated sand, investigating the relevant parameters governing pile installation geometry and pile depth of embedment, in order to simulate offshore torpedo piles. The work was developed in the laboratory through a series of model tests a pile installed, in both medium and dense sands, applying downwardly directed vertical water jets. Experimental results have shown that the fluidized geometry is not influenced by soil initial density. During pile installation, the perturbed zone covers a distance of two external diameters from the pile centreline, independent of the applied flow rate. By equating gravitational and upward drag forces on sand particles through Froude number, an expression for the fluidized zone is derived, which is shown to be correlated with fluidization water jet flow rate, as well as the soil and fluid properties. The critical depth of installation of fluidized piles is expressed as a function of the fluidized zone, and it ranges from 15 times the pile diameter until more than 50 times of it, being dependent on the actual combination of fluidized and soil parameters, as well as the pile geometry. Highlights: The geometry of fluidized cavities is not influenced by the initial density. During pile installation, the geometry of fluidized cavities is about 2 diameters and independent of the applied flow rate. An expression for the fluidized zone is suggested correlating the water jet flow rate, the soil and fluid properties. The critical depth of installation is expressed as a function of the fluidized zone. The critical depth of installation ranges from 15 times the pile diameter until more than 50 times of it.